- #1

Pedroski55

- 9

- 1

- TL;DR Summary
- Gp→Gl is true since the conditional in which the antecedent is false is always true. (Agnishom does not play the guitar).

I'm just learning some basic predicate logic. I found this.

Now this is changed to:

∃x (Gx→Gl), we have changed the scope of the quantifier to the entire expression. The sentence now means,

**UD:**People- Gx: x can play the guitar
- l: Lemmy

*If there is a guitarist, Lemmy is a guitarist*.Now this is changed to:

∃x (Gx→Gl), we have changed the scope of the quantifier to the entire expression. The sentence now means,

*There is a person x such that if x is a guitarist, Lemmy is a guitarist.*

I think I follow the above, but the next part:

You might notice that this sentence is true because non-Guitarists exist.

For example, let

Gp is FALSE (When p = Agnishom, I think)

I expected, only if Gx is true then (I think I follow the above, but the next part:

You might notice that this sentence is true because non-Guitarists exist.

For example, let

**p**be Agnishom. Gp→Gl is true**since the conditional in which the antecedent is false is always true**. (Agnishom does not play the guitar). Since someone, namely p, satisfies the sentence, ∃x(Gx→Gl) is true.Gp is FALSE (When p = Agnishom, I think)

I expected, only if Gx is true then (

*Gx→Gl) is true.*

Why is (Why is (

*Gp→Gl) TRUE when Gp is FALSE??**(Agnishom does not play the guitar)*

Thanks for any tips or pointers. I want to understand this before I continue. It seems important.Thanks for any tips or pointers. I want to understand this before I continue. It seems important.